Thermal fatigue mechanism of recrystallized tungsten under cyclic heat loads via electron beam facility. (December 2016) - Wang, Liang; Wang, Bo; Li, Shu-Dan; Ma, Dong; Tang, Yun-Hui; Yan, Hui
Abstract: Thermal fatigue resistance of plasma facing materials (PFMs) is an inevitable concern for component lifetime and plasma operations, since the temperature fluctuations will always exist in future nuclear fusion facilities and reactors. Accordingly, experiments were performed in the electron beam facility to investigate the thermal fatigue behavior under operational loading conditions. The tungsten is investigated in its stress relieved and fully recrystallized state for a better understanding of the thermal fatigue process when exposed to cyclic heat loads. The heat loads range from 24 to 48 MW/m 2 and the number of cycles increases from 100 to 1000 times. The results indicate that the thermal fatigue damage (surface roughening) due to plastic deformation strongly depends on the loading conditions and the cycle index. As the power density and the number of cycles increase, the density of the intragranular shear bands in each grain becomes higher and the swelling of grain boundaries becomes more pronounced. The shear bands are generally parallel to different directions for varying grains, showing strong grain orientation dependence. Additionally, extruded flake structures on shear bands were observed in these damaged areas. It found that the shear bands are generally parallel to the traces of {112} slip planes with the surface. The results suggest that slip plastic deformation represent the predominant mechanism for thermal fatigue and a set of schematic diagram is presented to explain the formation of thermal fatigue damage morphology (extrusion and intrusion structures). Highlights: Thermal fatigue damage depends on power density and pulse numbers. Shear bands were observed in damaged areas. The extruded flake structures on shear bands were formed. Shear bands are generally parallel to the traces of {112} slip planes with the surface.